Use of folk art to increase students' activity in the educational process (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article provides information about the use of folklore to increase the activity of students in the educational process and the integration of folklore into education is a powerful tool for increasing the activity and interest of students in learning